2017
DOI: 10.1111/mpp.12496
|View full text |Cite
|
Sign up to set email alerts
|

The APSES transcription factor Vst1 is a key regulator of development in microsclerotium‐ and resting mycelium‐producing Verticillium species

Abstract: SUMMARYPlant pathogens of the genus Verticillium pose a threat to many important crops worldwide. They are soil-borne fungi which invade the plant systemically, causing wilt symptoms. We functionally characterized the APSES family transcription factor Vst1 in two Verticillium species, V. dahliae and V. nonalfalfae, which produce microsclerotia and melanized hyphae as resistant structures, respectively. We found that, in V. dahliae Dvst1 strains, microsclerotium biogenesis stalled after an initial swelling of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 95 publications
2
31
0
Order By: Relevance
“…In V. dahliae , TFs such as VdSge1 also exhibit pleiotropic effects, including the requirement for radial growth, conidial production and pathogenicity (Santhanam and Thomma, ). Vdpf regulates melanized microsclerotia formation, conidial production and pathogenicity (Luo et al ., ), and Vst1 controls melanin biosynthesis, morphogenesis and secondary metabolism (Sarmiento‐Villamil et al ., ). In contrast, the phenotypes of all VdFTF1‐ deletion strains were similar to that of the wild‐type strain during cultivation on PDA medium, and they also exhibited similar conidial morphology and production (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…In V. dahliae , TFs such as VdSge1 also exhibit pleiotropic effects, including the requirement for radial growth, conidial production and pathogenicity (Santhanam and Thomma, ). Vdpf regulates melanized microsclerotia formation, conidial production and pathogenicity (Luo et al ., ), and Vst1 controls melanin biosynthesis, morphogenesis and secondary metabolism (Sarmiento‐Villamil et al ., ). In contrast, the phenotypes of all VdFTF1‐ deletion strains were similar to that of the wild‐type strain during cultivation on PDA medium, and they also exhibited similar conidial morphology and production (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…As our understanding of the pathogenicity of V. dahliae increases, it appears that a variety of genes are required for virulence towards host plants, including protein kinases (Rauyaree et al ., ; Tian et al ., ; Tzima et al ., ), TFs (Luo et al ., ; Santhanam et al ., ; Sarmiento‐Villamil et al ., ; Tran et al ., ; Xiong et al ., ), effectors (de Jonge et al ., ; Liu et al ., ; Santhanam et al ., ), enzymes involved in plant cell wall degradation (Chen et al ., ; Liu et al ., ; Maruthachalam et al ., ) and other functional genes (Gao et al ., ; Klimes and Dobinson, ; Li et al ., ; Maruthachalam et al ., ; Santhanam et al ., ; Zhang DD et al ., ; Zhang YL et al ., ). In this study, we identified a new pathogenicity and virulence‐related gene encoding a Fungal_trans domain‐containing TF (Figs and ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations